PERBANDINGAN MODEL PROJECT BASED LEARNING DAN PROBLEM BASED LEARNING DENGAN BERBANTUAN MEDIA CHEMSKETCH TERHADAP HASIL BELAJAR PADA MATERI IKATAN KIMIA - Tita Juwitaningsih; Agil Makarim Pane (FKIP University of Mataram, 2025)
This study is an experimental study that aims to measure the differences in student learning outcomes taught using the project-based learning and problem-based learning models. The study was conducted at SMA Negeri 1 Percut Sei Tuan in the 2024/2025 academic year. The population in this study were all class X students of SMA Negeri 1 Percut Sei Tuan. Sampling was carried out using random sampling techniques and the classes used were class X-6 as experimental class I and class X-8 as experimental class II. The independent variables are the project-based learning and problem-based learning models. The dependent variable is student learning outcomes in chemical bonding material. The research design used is the pretest-posttest control group design. Data collection was carried out by giving 20 questions with five answer choices. The average student learning outcomes in experimental class I were 81.76 and the average student learning outcomes in experimental class II were 74.55. The requirements for parametric testing on questions are normally distributed and homogeneous so that hypothesis testing can be carried out using a two-tailed t-test. The results of the hypothesis test with a two-tailed t-test obtained a sig value (2-tailed) of 0.001 at a significance level of α = 0.05. Based on the results of the hypothesis test, it can be concluded that there is a significant difference in learning outcomes in the chemical bond material learned using the project-based learning model and the problem-based learning model.